Sarcoidosis Revealed with Skin Manifestations and Acute Arthritis - Hatice Reşorlu; Sevilay Kılıç; Coşkun Zateri (Galenos Yayinevi, 2019)
A 37-year-old female patient admitted to our clinic with swelling in both knees and ankles and eruptions in her body. The patient was examined for the etiology of arthritis. In the biopsy taken from the plaque lesions on the skin, granulomatous sarcoidal lesions were detected. The case was diagnosed as sarcoidosis along with clinical, laboratory, and radiological findings. Sarcoidosis started with skin involvement is rarely seen in the literature. Biopsy from specific skin lesions allows diagnosis without the need for an invasive transbronchial biopsy. Therefore, we aimed to present a case of sarcoidosis diagnosed with skin manifestations.